EFEKTIFITAS TERAPI MASSAGE DAN HIDROTERAPI TERHADAP PENURUNAN INSOMNIA PADA LANSIA - Sari, Nadia; Wahidanur, Wahidanur; Abqariah, Abqariah; Makruf, Hafizul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
The health problem that many elderly people face is insomnia. Treating insomnia with non-pharmacological therapy has the advantage of being a therapy that does not cause side effects and is relatively easy to use, such as massage therapy and hydrotherapy. This study aims to determine the effectiveness of massage therapy and hydrotherapy in reducing insomnia in the elderly. The method used by the Quasy Experiment was a one-group pretest-posttest design with a sample size of 10 elderly people. The results obtained from statistical tests show that there is a difference in scores in the level of insomnia reduction before and after being given massage therapy and hydrotherapy, with p-value 0.000 (p-value 0.05), these results show that massage therapy and hydrotherapy are proven to be effective in reducing the level of insomnia in the elderly. It is hoped that the public will be aware and know the importance of massage therapy and hydrotherapy, especially for the elderly so that later they can carry out massage therapy and hydrotherapy therapy independently.Keywords : Massage, Hydrotherapy, Insomnia